Promoting daily physical activity in Norway as a FYSAK school: a comparative longitudinal study of lower secondary school pupil - Barth Vedøy, Ingeborg; Skulberg, Knut Ragnvald; Johansen, Patrick Foss; Tjomsland, Hege Eikeland; Thurston, Miranda (Frontiers in Sports and Active Living, 2025)
BackgroundSchools have been described as “ideal settings” for promoting PA, but they have struggled to find effective and sustainable ways of doing so given the demands of the curriculum. In Norway, the FYSAK school model is an example of a population approach to PA promotion wherein daily PA is embedded into the routines of the school. Little is known about the extent to which the model supports pupils' daily PA, especially with regard to meeting the national recommendations. The paper addresses the following research question: what impact does the FYSAK model have on pupils' PA patterns over time?MethodsThe paper draws on device-measured PA data from a three-year (2016–2018) longitudinal study of lower secondary school pupils from 11 schools in Norway, of which one was a FYSAK school. Data from 535 adolescents (56.1% female, mean age at baseline ± SD 13.3 ± 0.3 years) was derived and used to compare the PA level (cpm−1) of the one FYSAK school in the sample with the other 10 schools.ResultsThere was no difference in PA level between category of school in 2016. In 2017 and 2018 however, pupils attending the FYSAK school had significantly higher levels of PA compared to control schools (2017: 54.7 cpm−1, p ≤ .05, 2018: 59.2 cpm−1, p ≤ .05). Analyses of weekdays only, reinforced this pattern where larger differences in PA level across category of schools became evident (2017: 73.5 cpm−1, p ≤ .001, 2018: 85.7 cpm−1, p ≤ .001). Pupils attending the FYSAK school were also significantly more likely to adhere to the national recommendations for PA compared to control schools throughout all three years (2016: 57% FYSAK vs. 41% control, 2017: 62% FYSAK vs. 38% control, 2018: 52% FYSAK vs. 30% control).ConclusionsOverall, the results are indicative of a FYSAK school effect, which can be explained in terms of the sustained embedding of PA into pupils' daily routines over a three-year period. We conclude that the FYSAK model offers a framework for systematically providing realistic opportunities for being physically active during the school day.